2019
DOI: 10.1039/c9ra08752d
|View full text |Cite
|
Sign up to set email alerts
|

A walk around the application of nanocatalysts for cross-dehydrogenative coupling of C–H bonds

Abstract: Cross-dehydrogenative coupling reactions between two unmodified C–H bonds are one of the most attractive and fundamental strategies for the construction of C–C bonds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 112 publications
1
11
0
Order By: Relevance
“…TEM images indicated spherical NPs of size range 8-12 nm. STEM-HADF images of CB [7]NPs indicated interplanar spacing (2.54 Å) that matches with the d-spacing value of (2 2 0) plane of magnetite, while after palladium incorporation, two different plane spacings of 2.2 Å and 2.5 Å were observed that are characteristic of the (1 1 1) and (2 2 0) planes of Pd(0) and γ-Fe 2 O 3 respectively. The magnetic behavior displayed strong superparamagnetic signals at 4.9 × 10 8 M.U.…”
Section: Fe/cucurbituril With Pd For the Suzuki Sonogashira And Hecksupporting
confidence: 57%
See 4 more Smart Citations
“…TEM images indicated spherical NPs of size range 8-12 nm. STEM-HADF images of CB [7]NPs indicated interplanar spacing (2.54 Å) that matches with the d-spacing value of (2 2 0) plane of magnetite, while after palladium incorporation, two different plane spacings of 2.2 Å and 2.5 Å were observed that are characteristic of the (1 1 1) and (2 2 0) planes of Pd(0) and γ-Fe 2 O 3 respectively. The magnetic behavior displayed strong superparamagnetic signals at 4.9 × 10 8 M.U.…”
Section: Fe/cucurbituril With Pd For the Suzuki Sonogashira And Hecksupporting
confidence: 57%
“…Trabolsi and Guenin reported the curburbit [7]uril modified iron oxide nanoparticles [CB(7)NPs] loaded with palladium nanocatalysts for the microwave mediated Suzuki-Miyaura, Sonogashira and Mizoroki-Heck cross-coupling reactions in ethanolwater as solvent (Scheme 80). [58] By mixing excess of CB [7] with iron-oxide NPs in water at pH of 2 and 50°C provided solid support in which palladium acetate was absorbed.…”
Section: Fe/cucurbituril With Pd For the Suzuki Sonogashira And Heckmentioning
confidence: 99%
See 3 more Smart Citations